Social determinants of drug abuse among youth in Selangor: a case study in Serendah's Rehabilitation Centre / Shahera Nadia Sulaiman and Azizan Zainuddin - Sulaiman, Shahera Nadia; Zainuddin, Azizan (Universiti Teknologi MARA, 2021)
Drug abuse is considered one of the social issues in Malaysia. Despite various actions and initiatives taken by the Malaysian government, according to the data from MAMPU, the number of people abusing drugs keeps on increasing each year, especially among youth. Thus, this paper aims to identify the social determinants influencing drug abuse among youth in Selangor. This study found that the number of youths in Selangor involved in drug abuse is higher than other states in Malaysia. One hundred fortythree respondents participated in this quantitative study. The data was obtained by distributing questionnaires to youth aged between 19 to 39 years old, receiving treatment at the Serendah's rehabilitation centre when this study was being conducted. The age range was chosen based on youth defined in the Youth Societies and Youth Development Act 2007. The findings found that three factors contribute to youth involvement in drug abuse: peer influence, family environment, and neighbourhood influence. This study employed the Statistical Package for Social Sciences (SPSS) to analyse the data. This study provides several recommendations and a conclusion based on the outcomes.